2002
DOI: 10.1002/ana.10262
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity in old age: Sustained fivefold induction of hippocampal neurogenesis by long‐term environmental enrichment

Abstract: Neurons are continually born from endogenous stem cells and added to the dentate gyrus throughout life, but adult hippocampal neurogenesis declines precipitously with age. Short-term exposure to an enriched environment leads to a striking increase in new neurons, along with a substantial improvement in behavioral performance. Could this plastic response be relevant for explaining the beneficial effects of leading "an active life" on brain function and pathology? Adult hippocampal neurogenesis in mice living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
503
2
26

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 794 publications
(562 citation statements)
references
References 64 publications
31
503
2
26
Order By: Relevance
“…Environmental enrichment has been known for five decades to nurture early brain development. Kempermann et al (2002) observed a dramatic increase in new neurons in mice 10 months of age living in a typical enriched environment for rodents (playmates and toys) for 10 months. Moreover, their performance on a battery of behavioral assays also exceeded those of the controls housed under standard conditions.…”
Section: Location Locationmentioning
confidence: 95%
“…Environmental enrichment has been known for five decades to nurture early brain development. Kempermann et al (2002) observed a dramatic increase in new neurons in mice 10 months of age living in a typical enriched environment for rodents (playmates and toys) for 10 months. Moreover, their performance on a battery of behavioral assays also exceeded those of the controls housed under standard conditions.…”
Section: Location Locationmentioning
confidence: 95%
“…For example, reducing circulating levels of corticosteroids in adult rats by adrenalectomy has been shown to restore neural progenitor proliferation and neurogenesis (Cameron and McKay, 1999) and increasing the declining levels of insulin growth factor 1 (IGF-1) in aged rodents promotes adult neurogenesis and stem-celldependent muscle regeneration (Lichtenwalner et al, 2001;Musaro et al, 2004). In further support of reversible alterations to stem cell function in some tissues, changes in external stimuli, such as exposure to an enriched social environment (Kempermann et al, 1998b(Kempermann et al, , 2002 or physical exercise (Kronenberg et al, 2006;Lugert et al, 2010), improve age-related declines in NSC proliferation and neurogenesis. Taken together, Figure 1 Mechanisms of stem cell aging.…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%
“…We initially used a standard strategy for processing brain tissue for immunohistochemical analyses of inflammatory markers Kraig, 1996 , 1998;. However in these preliminary studies, animals from a modestly enriched environment had corticosterone levels of 150 ± 25 ng/ml (n = 9), values that might be more consistent with stress (Diamond et al, 1992) than with environmental enrichment (Kempermann et al, 2002;Kraig et al, 2003) (Fig. 1).…”
Section: Serum Corticosteronementioning
confidence: 99%
“…As a result, we changed our harvest procedures to a group-anesthesia format that would be conducive for use with animals housed as a group in typical environmental enrichment paradigms (Kempermann et al, 2002;Kraig et al, 2003). Animals harvested using this protocol had serum corticosterone levels of 62 ± 4 ng/ml (n = 9), values that while elevated from normal are consistent with environmental enrichment (Kempermann et al, 2002;Kraig et al, 2003). This is more than a two-fold and significant (P < 0.007, Mann-Whitney rank sum) decrease in mean corticosterone level and nearly a six-fold drop in variance.…”
Section: Serum Corticosteronementioning
confidence: 99%